2021
DOI: 10.1002/jemt.23855
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of curved root canals filled with a new bioceramic sealer: A microcomputed tomographic study using images with different voxel sizes and segmentation methods

Abstract: The aim of this study was to investigate the filling ability of a new premixed bioceramic sealer in comparison with an epoxy resin-based sealer in curved root canals using different segmentation methods and voxel sizes in micro-CT images. Twelve curved mesial roots of mandibular molars with two separated canals were selected.All root canals were prepared by using HyFlex EDM files size 25/.08 and filled by the single cone technique and Bio-C Sealer or AH Plus (n = 12). The samples were scanned by micro-CT at 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, the output quality was enough to identify and score the gap‐containing areas along the GP‐sealer interface using 2D transaxial images. Although some may argue that the pixel size used in this study is high, Pinto et al (2021) demonstrated that visual and automatic segmentation can be applied to micro‐CT images with voxel sizes from 5 to 20 µm to evaluate the filling of a sealer with radiopacity that complies with ISO 6876:2012 standard (ISO, 2012) such as the AH Plus (Silva et al, 2013) and EndoSequence BC Sealer (Candeiro et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, the output quality was enough to identify and score the gap‐containing areas along the GP‐sealer interface using 2D transaxial images. Although some may argue that the pixel size used in this study is high, Pinto et al (2021) demonstrated that visual and automatic segmentation can be applied to micro‐CT images with voxel sizes from 5 to 20 µm to evaluate the filling of a sealer with radiopacity that complies with ISO 6876:2012 standard (ISO, 2012) such as the AH Plus (Silva et al, 2013) and EndoSequence BC Sealer (Candeiro et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…All students performed root canal filling using two techniques and three sealers under a dental operating microscope. Based on the data of previous studies, 3 , 11 the sample size was calculated using the G∗Power software 3.1.9.6 (Heinrich Heine, Universität Dusseldorf, Germany). The effect sizes of the data for comparison of technique and sealer were 1.62 3 and 0.85, 11 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the data of previous studies, 3 , 11 the sample size was calculated using the G∗Power software 3.1.9.6 (Heinrich Heine, Universität Dusseldorf, Germany). The effect sizes of the data for comparison of technique and sealer were 1.62 3 and 0.85, 11 respectively. Therefore, the data with smaller effect size (0.85) was selected to calculate the sample size, which was determined to be 18 for each group when α = 0.05, 1 − β = 0.8, which can yield the actual power of 0.8.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the most ideal treatment for pulpitis and periapical periodontitis is root canal therapy, but in the process of root canal therapy, patients often have a certain degree of pain, intraoperative pain leads to patients being unable to cooperate with the doctor to complete the operation and even interrupts the treatment, and the patients refuse to see a doctor again. This kind of pain and discomfort can lead to anxiety, depression, irritability, and negative rebellious coping style; bad emotional state and coping strategies worsen doctor-patient relationship, reduce patients' trust in doctors, and patients evading treatment [ 4 ]. Therefore, the oral health condition is getting worse and worse, the quality of life cannot be guaranteed, and the well-being index of life is greatly reduced [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%